A randomized, single-blind, study evaluating a 755-nm picosecond pulsed Alexandrite laser vs. a non-ablative 1927-nm fractionated thulium laser for the treatment of facial photopigmentation and aging. (18th August 2018) - Serra, Monica; Bohnert, Krista; Sadick, Neil
ABSTRACT: Background : Laser toning is one of the most popular strategies to treat facial photopigmentation and aging. Several laser modalities, including fractional non-ablative, Q-switched (QS) lasers and new generation picosecond lasers have been used for this indication. However, there is paucity of head to head comparisons of older generation of lasers with new ones. Objective : To compare a 755 nm picosecond pulsed alexandrite laser with a non-ablative 1927 nm fractionated thulium laser for the treatment of facial photopigmentation and aging through a randomized, single-blind study. Materials and methods : 20 subjects (skin types I–IV) were randomized to receive either four 755-nm picosecond alexandrite laser treatments, spaced 3 weeks apart, or two dual wavelength thulium fiber fractionated 1550/1927 nm laser treatments, spaced 6 weeks apart. Follow-up assessment visits occurred 4 and 12 weeks after the last study treatment. Results : At the 4- and 12-week follow-up, both groups showed significant improvement of photoaging, pigmentation, skin quality according to the investigator and subjects assessments. When comparing the two groups, subjects in 755 nm group had statistically significant greater improvement in investigator assessments of photoaging/skin quality and subject satisfaction than those in the 1927 nm group. Conclusion : Both the non-ablative 1927 and 755 nm picosecond laser can improve facial photopigmentation, but the latter can yield superior results with less pain and side effects according to patient and investigator assessments.